Easy-Tracing Environmental Measures under WTO Law - Yohanes Hermanto Sirait; Arie Afriansyah; Tran Viet Dung (Lampung Journal of International Law, 2025)
The intersection between trade and environmental issues has become an unavoidable reality in the contemporary global landscape. The WTO, as the foremost global trade body, integrates elements of sustainable development across several of its legal frameworks. This study seeks to explore the presence and evolution of environmental measures within the framework of the WTO. This research further examines the practical recognition of environmental measures within international trade contexts. Through normative research and comparative case studies of state disputes in WTO’ Dispute Settlement Body, this study identifies a growing trend in the use of environmental measures within WTO legal frameworks. The findings indicate that environmental measures possess a degree of legitimacy and are generally well-received by the WTO dispute settlement mechanism. Ambitious emission targets set by developed countries have contributed to the development of novel types of environmental measures.This indicates that the interconnection between trade and environmental concerns will continue to strengthen over time. Hence, ensuring a well-calibrated balance between trade obligations and environmental considerations requires the panel or Appellate Body to proceed with heightened prudence..